Structural Model of Predicting Rumination in Individuals with Generalized Anxiety Disorder Based on Integrative Self-Knowledge and Mentalization: The Mediating Roles of Psychological Flexibility and Distress Tolerance - Bakhtiarizadeh , Masoumeh; Ebrahim Montazeri, Seyed Mohammad (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to develop and test a structural model for predicting rumination among individuals with Generalized Anxiety Disorder (GAD) based on integrative self-knowledge and mentalization, considering the mediating roles of psychological flexibility and distress tolerance. This applied, descriptive-correlational study was conducted among university students diagnosed with Generalized Anxiety Disorder in Qom, Iran, during 2025. A purposive sample of 270 participants was selected based on predefined inclusion criteria. Data were collected using the Integrative Self-Knowledge Scale, Mentalization Scale, Acceptance and Action Questionnaire-II, Distress Tolerance Scale, and Ruminative Responses Scale. Structural equation modeling and path analysis were performed using SPSS-23 and AMOS-23 to examine the direct and indirect relationships among the study variables and to evaluate the proposed structural model. The findings indicated that rumination was directly and negatively predicted by integrative self-knowledge (β = −0.265, p = .001), mentalization (β = −0.253, p = .001), distress tolerance (β = −0.297, p = .001), and psychological flexibility (β = −0.204, p = .001). Integrative self-knowledge positively predicted distress tolerance (β = 0.219, p = .001) and psychological flexibility (β = 0.176, p = .001). Similarly, mentalization positively predicted distress tolerance (β = 0.267, p = .001) and psychological flexibility (β = 0.378, p = .001). Significant indirect effects were observed for integrative self-knowledge (β = −0.101, p = .034) and mentalization (β = −0.156, p = .001) on rumination through the mediating variables. The results suggest that higher levels of integrative self-knowledge and mentalization contribute to lower levels of rumination among individuals with GAD both directly and indirectly through enhanced psychological flexibility and distress tolerance.